If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5u + 1)(3 + -1u) = 0 Reorder the terms: (1 + 5u)(3 + -1u) = 0 Multiply (1 + 5u) * (3 + -1u) (1(3 + -1u) + 5u * (3 + -1u)) = 0 ((3 * 1 + -1u * 1) + 5u * (3 + -1u)) = 0 ((3 + -1u) + 5u * (3 + -1u)) = 0 (3 + -1u + (3 * 5u + -1u * 5u)) = 0 (3 + -1u + (15u + -5u2)) = 0 Combine like terms: -1u + 15u = 14u (3 + 14u + -5u2) = 0 Solving 3 + 14u + -5u2 = 0 Solving for variable 'u'. Factor a trinomial. (3 + -1u)(1 + 5u) = 0Subproblem 1
Set the factor '(3 + -1u)' equal to zero and attempt to solve: Simplifying 3 + -1u = 0 Solving 3 + -1u = 0 Move all terms containing u to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -1u = 0 + -3 Combine like terms: 3 + -3 = 0 0 + -1u = 0 + -3 -1u = 0 + -3 Combine like terms: 0 + -3 = -3 -1u = -3 Divide each side by '-1'. u = 3 Simplifying u = 3Subproblem 2
Set the factor '(1 + 5u)' equal to zero and attempt to solve: Simplifying 1 + 5u = 0 Solving 1 + 5u = 0 Move all terms containing u to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5u = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5u = 0 + -1 5u = 0 + -1 Combine like terms: 0 + -1 = -1 5u = -1 Divide each side by '5'. u = -0.2 Simplifying u = -0.2Solution
u = {3, -0.2}
| A+6=-12 | | 7(x+3)-(6x-9)=12 | | f=-5+g | | -3w+1=38 | | 1.5b+4=5 | | 0.5(4z+0.25)=2(z+1.16) | | x+(x-3.5)=65.5 | | 7x-5+3=4x-20 | | 16-3w=58 | | (37*x)*.6=77.7 | | -26=2y+4(y+7) | | 17=k+4 | | x=-3(x+n) | | 14a+-93=49+57a | | -10=8-x*7 | | -21=7u+7(u-7) | | 3(6z+7)+10z+45=180 | | 4x^2-7x-57=0 | | (2x-30)=45 | | (x^2-1)=0 | | w-16=-3 | | x+(x+4)=50 | | 4x-19=13x-1 | | 2(x-6)=7 | | 3(6z+7)10z+45=180 | | 2/3(3x+1)=5 | | -1.25+0.5x=0 | | 9x-7=12x-4 | | 3x*3y= | | 20+8(a-11)=-12 | | 9x-7=12-4 | | x^2+8xy+16y^2-4x-16y+7=0 |